(untitled) (Eurasian Medical Research Periodical, 2022)
Components of a metabolic syndrome meet much more more often among smokers, than at non-smoking. Among the studied group smokers make 65,7% and all of them a male, among them them men at the age of 51-60 years prevail. Among smokers the most widespread component of a metabolic syndrome is the arterial hypertonia (47,8%), the increased tolerance to carbohydrates (43,5%). Keywords: overweight, smoking, metabolic syndrome, arterial hypertonia